Correct Outcome Prognostication via Sonographic Volumetry in Supratentorial Intracerebral Hemorrhage - Niesen, Wolf-Dirk; Schlaeger, Axel; Bardutzky, Juergen; Fuhrer, Hannah (Frontiers in Neurology, 2019)
Introduction: The intracranial hemorrhage (ICH)-score is used for estimation of patients’ prognosis. The hemorrhage volume calculated from computed tomography (CT) contributes as one main factor. Several studies have proven that dimensions of an ICH may be displayed sufficiently by transcranial sonography (TCS). Yet, the adequacy of ICH-volumetry via TCS in calculating the ICH-score and its use as prognostic tool has not been studied. Methods: 40 consecutive patients with supratentorial ICH diagnosed via CT were included in this prospective observational pilot study. 45 examination-series via CT and TCS were done in order to perform an ICH-volumetry and calculate the ICH-score. Volume was calculated using the ABC/2 estimation. Results of both imaging techniques were compared regarding quantification of ICH- volume and correct prognostication. A modified Rankin Scale (mRS)-score of 0-3 points was valued as good outcome. Results: The imaging techniques did not show a difference in volumetry (p=0.794) and TCS derived hemorrhage volume correlated significantly with ICH-volume measured on CT-scans. Calculated ICH-scores also did not differ (p=0.323). Patients with an ICH-score larger than 2 points were predicted to experience a poor outcome at discharge with mRS 4-6 points, and the prognostication of the outcome was correct. Patients with a good outcome showed a smaller ICH-volume (11.2±9.1ml) than patients with a poor outcome (38.2 ±41.2ml; p=0.002). Conclusion: Volumetry in supratentorial ICH via TCS is feasible and the prognostication with the ICH-score based on its results is comparable to CT-imaging and sufficient.